Expression and role of regulator of G‐protein signaling 5 in squamous cell carcinoma of the tongue. Issue 2 (4th March 2019) - Abe, Yushi; Ogasawara, Sachiko; Akiba, Jun; Naito, Yoshiki; Kondo, Reiichiro; Nakamura, Ken; Kusukawa, Jingo; Yano, Hirohisa
Abstract: Regulator of G‐protein signaling (RGS) 5 acts as a GTPase‐activating protein to negatively regulate G‐protein signaling. RGS5 is reportedly related to the invasion and metastasis of cancers, such as nonsmall lung cancer and hepatocellular carcinoma. We examined RGS5 expression and its relationship with invasion in squamous cell carcinoma (SCC) of the tongue. For immunohistochemical analysis of RGS5, we used SCC tissues of the tongue obtained from 43 patients. We examined the relationship between RGS5 expression in the deepest point of invasion and clinicopathological features. Because the invasion and metastasis of cancers are related to epithelial‐mesenchymal transition (EMT), we carried out staining for N‐cadherin, vimentin, and E‐cadherin to examine the relationship between EMT and RGS5. RGS5 expression in the deepest point of invasion in SCC of the tongue was observed in 32 cases (75%). Immunohistochemical analysis revealed a significant correlation between RGS5 expression in the aggressive invasion pattern, invasion depth, and lymphovascular invasion. Kaplan–Meier analysis revealed that high RGS5 expression was associated with postoperative early lymph node metastasis. Further, a significant positive correlation was observed between RGS5 and N‐cadherin ( P = 0.0003) and vimentin ( P < 0.0001). In contrast, E‐cadherin and RGS5 or vimentin were significantly negatively correlated ( P < 0.0001–0.005). The findings indicate that RGS5 expression is related to tumor invasion and EMT in SCC of the tongue and that RGS5 may predict postoperative early lymph node metastasis. Therefore, RGS5 may be a useful prognostic biomarker of the surgically resected SCC and a potential target of molecular therapy for treating SCC of the tongue.